Relationship between Affective Dimension and Math Learning - Ronny Gamboa Araya (Universidad Nacional, Costa Rica, 2014)
Math has become an obstacle to achieve educational goals for a large number of students; thus it has transcended the academic world and has become a cognitive and emotional impairment.  What students feel, perceive, believe, and how they act directly influences this.  In addition, what teachers feel and perceive, their expectations, beliefs and attitudes towards the discipline also play an important role in how they teach and in the affective dimension of their students.  Based on theoretical aspects from various authors, this paper is aimed at addressing some elements regarding the affective dimension, and at showing elements pertaining to teachers and students, and their relationship with math learning and teaching.  It was concluded that the role of the affective dimension in math learning must be addressed by math educators in order to understand the process from the perspective of the actors associated with it, both students and teachers, as well as to achieve a change in the discipline by improving the beliefs and attitudes of students and teachers.